The Shadow of Deficiency: Vitamin D Status as a Critical Determinant of Antithyroid Drug Efficacy in Graves’ Disease – Insights from an Indonesian Cohort - Ratna Maila Dewi Anggraini; Intan Fajrin Karimah; Eddy Yuristo; Yulianto Kusnadi; Erwin Sukandi (HM Publisher, 2025)
Background: Graves' disease (GD), an autoimmune hyperthyroid condition, presents significant management challenges, particularly concerning variable remission rates with antithyroid drugs (ATDs). Vitamin D, with its established immunomodulatory properties, is hypothesized to influence autoimmune processes, including those in GD. However, its precise impact on ATD treatment outcomes in diverse populations, especially in regions like Indonesia with high vitamin D deficiency prevalence, remains insufficiently elucidated. Methods: This retrospective cohort study was conducted at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia, analyzing data from 73 newly diagnosed adult GD patients (diagnosed January 2022 - December 2023). Patients had confirmed GD based on hyperthyroidism with orbitopathy or positive TRAb and were followed until May 2025. Baseline serum 25-hydroxyvitamin D [25(OH)D], free T4 (fT4), and TSH levels were recorded. Vitamin D deficiency (VDD) was defined as <20 ng/mL. The primary outcome was non-remission after ATD therapy, defined as failure to achieve stable euthyroidism for ≥6 months on minimal ATD doses. Multivariate Poisson regression was used to assess predictors of non-remission. Results: Of 73 patients (mean age 36.2 years; 62% female), 55 (75.3%) exhibited VDD. Multivariate analysis identified VDD as a significant independent predictor of non-remission (adjusted Relative Risk [aRR] 11.81; 95% CI 1.88–74.20; p=0.008). Elevated baseline fT4 levels (≥5 ng/dL; aRR 4.61; 95% CI 1.13–18.70; p=0.032) and older age (>48 years; aRR 0.078; 95% CI 0.06–0.95, indicating a protective effect of older age against non-remission) were also significant predictors. Conclusion: Baseline vitamin D deficiency is a potent independent risk factor for non-remission in Indonesian Graves' disease patients receiving antithyroid drug therapy. These findings underscore the potential importance of assessing and addressing vitamin D status in the management of Graves' disease to optimize therapeutic outcomes.